Health services in Nordic welfare states: Introducing a new category of providers through the Norwegian free treatment choice reform. Issue 5 (October 2022) - Lindén, Tord Skogedal; Ervik, Rune
Aim : We contribute to the literature on private provision of health care in Nordic countries by studying developments following the 2015 Norwegian free treatment choice reform. The reform introduced new providers of publicly financed health care. These new private for-profit or not-for-profit providers are licensed by Helfo (the Norwegian Health Economics Administration) to offer pre-defined services at pre-defined prices. They treat patients referred to specialist health care given that patients choose these providers. We focus on multidisciplinary specialist substance treatment and mental health care, areas constituting 78% of reform costs in 2019.Methods and data : We discuss three sets of questions with statistics, documents, and interview data: What developments and consequences of new providers did key actors expect? What developments of Helfo-licensed providers do we see and why? How have Helfo-licensed providers influenced collaboration between public and non-public providers and recruitment?Results : Contrary to expectations, we found that most Helfo-licensed providers have not previously collaborated with public providers through tender agreements. This complicates collaboration. So far, the establishment of new providers has not undermined public providers in terms of recruitment.Conclusion : Public providers with Helfo-licensed providers in their area still experience some pressure on recruitment and express concerns for future negative reform consequences. The introduction of new private providers may influence the level of market-orientation in the Norwegian welfare state.